A biomimetic biofilm-inspired hydrogel for enhanced ultraviolet- shielding and anti-scouring ability of microbial pesticides - Zeyu Wang; Qinghui Shen; Xiaoxu Ma; Zirong He; Colin Berry; Xiang He; Changlong Shu; Qiliang Huang; Ahmed Idris Hassen; Chong Cao; Jie Zhang (Chemical Engineering Journal, 2026)

Specificity database for bacterial pesticidal proteins against invertebrate targets - Colin Berry; Victoria Valby; Ruchir Mishra; Bryony C. Bonning; Leopoldo Palma; Neil Crickmore (Journal of Invertebrate Pathology, 2025)

Positive selection analysis of Cyt proteins from Bacillus thuringiensis: A conservative trend driven by negative (purifying) selection - Leopoldo Palma; Diego Herman Sauka; Colin Berry; Cecilia Peralta (Toxicon, 2024)

UV protection and insecticidal activity of microencapsulated Vip3Ag4 protein in Bacillus megaterium - Leopoldo Palma; Iñigo Ruiz de Escudero; Francisco Mañeru-Oria; Colin Berry; Primitivo Caballero (Toxicon, 2024)

In vitro acaricidal activity of several natural products against ibex-derived Sarcoptes scabiei - Jesús M. Pérez; Emiliano N. Jesser; Jorge O. Werdin; Colin Berry; Mohamed A. Gebely; Raquel Crespo-Ginés; José E. Granados; Antonio J. López-Montoya (Veterinary Parasitology, 2024)

Chemical ecology of nectar–mosquito interactions: recent advances and future directions - Islam S Sobhy; Colin Berry (Current Opinion in Insect Science, 2024)

Transgenic maize inbred lines expressing high levels of Bacillus thuringiensis vegetative insecticidal protein (Vip3Aa86) offer effective control of maize stem borer (Chilo partellus) - Muhammad Umar Bhatti; Bushra Tabassum; Colin Berry; Anwar Khan; Uzma Qaisar; Ejaz Ali; Rida Khalid; Abdul Munim Farooq; Muhammad Tariq; Hasan Ayaz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Letter to the Editors regarding “10% body weight (gain) change as criterion for the maximum tolerated dose: A critical analysis” - Sir Colin L. Berry; Samuel M. Cohen; J. Christopher Corton; Joao Lauro Viana de Camargo; Gerhard Eisenbrand; Shoji Fukushima; Helmut Greim; Klaus Weber; Ivonne M.C.M. Rietjens; Christian Strupp (Regulatory Toxicology and Pharmacology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Categorizing the characteristics of human carcinogens: a need for specificity - Carr J. Smith; Thomas A. Perfetti; A. Wallace Hayes; Sir Colin Berry; James E. Trosko; Judy A. King; Jay I. Goodman; C. Glenn Begley; Anthony Dayan (Archives of Toxicology, 2021)

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

The dangers of preemptive obedience to political pressure and media campaigns in science - Colin Berry (Archives of Toxicology, 2019)

Investigation of the Cry4B–Prohibitin Interaction in Aedes aegypti Cells - Atichat Kuadkitkan; Duncan R. Smith; Colin Berry (Current Microbiology, 2012)

Facilitating adaptation of biodiversity to climate change: a conceptual framework applied to the world’s largest Mediterranean-climate woodland - Suzanne M. Prober; Kevin R. Thiele; Philip W. Rundel; Colin J. Yates; Sandra L. Berry; Margaret Byrne; Les Christidis; Carl R. Gosper; Pauline F. Grierson; Kristina Lemson; Tom Lyons; Craig Macfarlane; et al. (Climatic Change, 2012)

The Cry48Aa‐Cry49Aa binary toxin from Bacillus sphaericus exhibits highly restricted target specificity - Gareth W. Jones; Margaret C. Wirth; Rose G. Monnerat; Colin Berry (Environmental Microbiology, 2008)
Summary The Cry48Aa/Cry49Aa binary toxin of Bacillus sphaericus was recently discovered by its ability to kill Culex quinquefasciatus mosquito larvae through a novel interaction between its two components. We have investigated the target specificity of this toxin and show it to be non‐toxic to coleopteran, lepidopteran and other dipteran insects, including closely related Aedes and Anopheles mosquitoes. This represents an unusually restricted target range for crystal toxins from either B. sphaericus or Bacillus thuringiensis. Gut extracts from Culex and Aedes larvae show differential processing of the Cry48Aa protein, with the location of cleavage sites in Culex reflecting those previously shown for the activation of Cry4 toxins in mosquitoes. Pre‐activation of Cry48Aa/Cry49Aa with Culex extracts, however, fails to induce toxicity to Aedes larvae. Co‐administration of Cry49Aa with Cry4Aa gives higher than predicted toxicity, perhaps suggesting weak synergism against Culex larvae between Cry49Aa and other three‐domain Cry toxins.

Effects on kidney disease, fertility and development in mice inheriting a protein-truncating Denys-Drash syndrome allele (Wt1 tmT396) - Charles E. Patek; David G. Brownstein; Stewart Fleming; Caroline Wroe; Lorraine Rose; Anna Webb; Rachel L. Berry; Paul S. Devenney; Marion Walker; Oliver D. K. Maddocks; Nicola J. Lawrence; David J. Harrison; et al. (Transgenic Research, 2008)